2022
DOI: 10.1021/acscatal.2c01544
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 Electromethanation on Surface-Modified Cu Catalyst by Local Microenvironment Modulation

Abstract: Renewable methane synthesized via CO2 electroreduction has the potential to serve as a carbon-neutral medium benefiting from its high energy density. However, challenges remain in achieving high selectivity for electromethanation with low energy input. Here, we found that the adhered ligands on the copper surface can modulate the local microenvironment to realize high rates for methane electrogeneration. The designed glutathione-modified copper electrode exhibited an impressive CO2 to CH4 Faradaic efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The poor stability of Cu-based materials results from serious degradation mechanisms such as fragmentation, reshaping, and agglomeration, , and the low selectivity is due to the uncontrollable oxidation state of Cu during the CO 2 RR procedure . Many kinds of strategies have been reported to solve these problems, such as controlling the surface structure, morphology, and oxidation state of the catalysts, doping various elements into the catalysts, optimizing the electrolyte ions and reaction pH, and designing the electrochemical cell. , Although these strategies enhance product selectivity, CO 2 RR stability and affordability still remain challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The poor stability of Cu-based materials results from serious degradation mechanisms such as fragmentation, reshaping, and agglomeration, , and the low selectivity is due to the uncontrollable oxidation state of Cu during the CO 2 RR procedure . Many kinds of strategies have been reported to solve these problems, such as controlling the surface structure, morphology, and oxidation state of the catalysts, doping various elements into the catalysts, optimizing the electrolyte ions and reaction pH, and designing the electrochemical cell. , Although these strategies enhance product selectivity, CO 2 RR stability and affordability still remain challenges.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, researches about electrocatalytic CO 2 reduction reaction (CO 2 RR) and electrocatalytic N 2 reduction reaction (NRR) have been mainly focused on the exploration of electrocatalysts since they improve the reaction rate, efficiency, and selectivity toward desired products. [16][17][18] A large number of publications show that numerous efforts have been made to design and construct the active sites on the surface of electrocatalysts to enhance the performance of CO 2 RR and NRR, including the regulation of crystal facets, [19][20][21] surface morphology, [22][23][24][25] particle size, [26][27][28] oxidation state, [29,30] and heteroatom doping. [31][32][33] Although these regulation methods have got some obvious advance, they cannot overcome the fatal flaws of overall electrocatalytic processes, including the low solubility of CO 2 and N 2 in electrolyte, and the competitive hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%
“…30 The S–H bands of BDT at 930.5 cm −1 and 2538.8 cm −1 disappeared in Cu NPs-BDT, which suggested that benzenethiol was attached to the Cu surface via a Cu–S bond. 30,31 S 2p XPS (Fig. 1c) of Cu NPs-BDT showed peaks at 165.3 eV and 164.1 eV attributed to the C–S bond and peaks at 162.7 eV and 163.9 eV corresponded to the Cu–S bond, consistent with FT-IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…1c) of Cu NPs-BDT showed peaks at 165.3 eV and 164.1 eV attributed to the C–S bond and peaks at 162.7 eV and 163.9 eV corresponded to the Cu–S bond, consistent with FT-IR spectroscopy. 31,32 Cu 2p XPS (Fig. S7†) results showed the presence of Cu 0 /Cu + species.…”
Section: Resultsmentioning
confidence: 99%